Hunter-fisher-gatherer pottery production and use at the Neolithic shell-midden of Riņņukalns, Latvia. (December 2021) - Spataro, Michela; Oras, Ester; Lucquin, Alexandre; Bērziņš, Valdis
Abstract: ABSTRACT: The shell-midden site of Riņņukalns in northern Latvia offers a rare opportunity to study long-term trends in ceramic production and function at a European hunter-fisher-gatherer site. Riņņukalns was occupied from the sixth millennium BC, with the midden developing from the later fourth millennium. Here, the authors discuss the chaîne opératoire and function of the Riņņukalns material, showing that pottery was used in both the pre-midden and midden phases primarily to cook aquatic and porcine resources. The technology used to produce these cooking vessels, however, changed over time, with new firing techniques associated with a shift to the use of shell temper. The results have implications for understanding prehistoric technology and subsistence in other parts of the world.